Plan de negocios para una empresa productora y comercializadora de forraje verde hidropónico (FVH), para alimentación de ganado caprino en la Parroquia Colonche, Cantón Santa Elena - Rodríguez Caiche, Omar Fabricio (2017)
Goats are small ruminants with the capacity to transform forages of different types, even those of poor quality such as cereal straw, residues and by-products from the garden, Santa Elena has a dry tropical climate which prevents the proliferation of natural grass, which is why has taken the initiative to produce hydroponic green fodder (FVH), this technology is a nutritional alternative for animals in monogastric and polygastric livestock farms in desert or semi-desert environments; the purpose of this work was to design a Business Plan for a production and marketing company of FVH in the parish of Colonche; for this, a descriptive investigation was carried out that allowed establishing the feasibility; before all this it was possible to conclude that the product has good acceptance, obtaining as a result that of 128 goat producers, 96.88% indicated to agree and acquire the product at a cost of $ 0.12 per kilogram; by evaluating the project, it was determined that the recovery period is 2 years and 8 months, with an IRR of 22.3%, considering values of raw materials used for the preparation of FVH and other expenses such as depreciation, labor , basic services and administrative expenses, it can be calculated that for every dollar invested to produce 1kg of FVH, the benefit / cost ratio is 1.27, that is, an economic benefit of $ 0.27 cents will be obtained for every dollar invested, It was also determined that to produce 1 kilogram of hydroponic green forage, it is necessary to invest $ 0.08.